ChatGPT and the Pedagogical Challenge: Unveiling the Impact on Early-Career Academics in Higher Education - FX Risang Baskara; Anindita Dewangga Puri; Annisa Radista Wardhani (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2023)
Emerging Artificial Intelligence (AI) tools like ChatGPT offer considerable promise for enhancing professional development in higher education. This study focuses on the experiences of early-career lecturers who utilise ChatGPT for professional development. Central questions explore ChatGPT's influence on their overall professional experience and the challenges and benefits of its use. While research on AI in education has been growing, few studies have delved into the specific experiences of young academics using ChatGPT. This study employed qualitative methods to address this gap, pre-cisely 45- to 60-minute in-depth interviews with two purposively selected lecturers, followed by a thematic analysis using a grounded theory approach. Our findings reveal a multifaceted landscape: on the one hand, ChatGPT enhances the ability to construct intricate academic arguments, increases effi-ciency in research and teaching tasks, and heightens critical thinking capabilities. Conversely, chal-lenges such as initial technical hurdles, occasional incorrect outputs, and concerns about over-dependency were also highlighted. Through this investigation, the study contributes to the broader discourse on AI in education by illustrating both the promising opportunities and potential pitfalls of using ChatGPT in academia. The study underscores the need for a balanced approach to AI adoption. It offers insights into the role of AI tools like ChatGPT in shaping the future of professional development in higher education.